Herbal mouthwash based on Libidibia ferrea: microbiological control, sensory characteristics, sedimentation, pH and density - Gisely Naura Venâncio; Isis Costa Rodrigues; Tatiane Pereira de Souza; Raquel de Oliveira Marreiro; Maria Fulgência Costa Lima Bandeira; Nikeila Chacon de Oliveira Conde
Introduction Phytotherapy is the study of herbal medicines and their applicability to cure diseases in general, being a therapeutic method which can be used for the prevention and treatment of mouth diseases. Among the herbal studied, the Libidibia ferrea, known as jucá or ironwood, is widely used in folk medicine by presenting anti-inflammatory, analgesic, antimicrobial and antipyretic therapeutic properties. Objective To evaluate in vitro pharmacological stability of the Libidibia ferrea extract's mouthwash (INPA - 228 022). Material and method It was held the mouthwash microbiological control by determining the total number of microorganisms and Salmonella sp, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus; stability characteristics (color, odor, brightness and consistency), sedimentation test (centrifuge), the pH measurement (pH meter) and density evaluation (pycnometer) were analyzed. Result The mouthwash showed to be absent from microorganisms and no changes were observed in the organoleptics and sedimentation characteristics. The average pH values were 6.21, 6.15 and 5.85 at 0, 30 and 60 days, respectively, and 1.029, 1.033 and 1.035 g/ mL density values, respectively, without interfering with the final characteristic of the formulation. Conclusion The mouthwash presented pharmacological stability and quality conditions.